2016
DOI: 10.1111/jmp.12215
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure as prognostic marker for body condition, cardiovascular, and metabolic diseases in the common marmoset (Callithrix jacchus)

Abstract: The description of age and weight influences on BP delivers physiological and pathological values for common marmosets. This may contribute to the understanding of aging process and cardiology in this primate species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
1
7
1
Order By: Relevance
“…Measures of blood pressure and hypertension are often a useful proxy to estimate the effects of age on cardiovascular health. Marmosets have previously been found to have significant age effects on mean arterial pressure and diastolic pressure, with no significant differences in systolic pressure (Mietsch et al, 2016;Mietsch & Einspanier, 2015). We have also found that mean arterial pressure and diastolic pressure were significantly associated with age, and no relationship with age was found for systolic pressure.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Measures of blood pressure and hypertension are often a useful proxy to estimate the effects of age on cardiovascular health. Marmosets have previously been found to have significant age effects on mean arterial pressure and diastolic pressure, with no significant differences in systolic pressure (Mietsch et al, 2016;Mietsch & Einspanier, 2015). We have also found that mean arterial pressure and diastolic pressure were significantly associated with age, and no relationship with age was found for systolic pressure.…”
Section: Discussionsupporting
confidence: 61%
“…Blood Pressure: All of the subjects were evaluated twice during the duration of this study for blood pressure using a high definition oscillometric device (VET HDO monitor MD PRO Marmoset; S+B medVET GmbH, Babenhausen, Germany) following (Mietsch et al, 2016). Marmosets were held in a gloved hand in a simulated quadrupedal position which allowed access to the right leg for each measurement.…”
Section: Homeostasismentioning
confidence: 99%
“…Taking an average life expectancy of about 12 years for marmosets in captivity, the age range of the marmosets included in this study corresponds to about 18 to 80 years in humans. Even though previous studies have reported higher risk of myocardial fibrosis [5,17] and increased blood pressure [24,25] with increasing age in marmoset, we observed only relatively mild disturbances of the cardiac function with age.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite the multifarious usage in different fields, comprehensive research on the immune system of this species is so far missing. While important parameters for health screening, for example, hematological, blood chemistry, metabolome and cardiovascular values are already established, a comprehensive overview of immunological parameters during different stages of age is still pending (Hoffman et al, 2016; Mietsch et al, 2016; Reveles, Patel, Forney, & Ross, 2019). On the other hand, extensive panels of cross‐reacting antibodies for flow cytometric analyses in the common marmoset have been reported (Brok, Hornby, Griffiths, Scott, & Hart, 2001; Neumann et al, 2016).…”
Section: Introductionmentioning
confidence: 99%